2005
DOI: 10.1212/01.wnl.0000168862.09764.9f
|View full text |Cite
|
Sign up to set email alerts
|

Association of the metabolic syndrome with intracranial atherosclerotic stroke

Abstract: To investigate the impact of metabolic syndrome (MetSD) on the development of intracranial atherosclerotic stroke, the authors evaluated the components of the MetSD in 512 patients with stroke. The MetSD was observed most frequently in patients with intracranial atherosclerosis (p = 0.007). In multiple regression analysis, the MetSD, but not conventional risk factors, was independently associated with intracranial atherosclerosis (p = 0.005). The results suggest that treatment of metabolic abnormalities may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
3
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 13 publications
9
81
3
6
Order By: Relevance
“…ICAS is more common in Asians than in Caucasians. 1 Previous studies have addressed the differences in risk factors between ICAS and extracranial atherosclerosis to provide a possible explanation for the racial difference, but the results have been inconsistent; reports that hypertension, 2,3 diabetes mellitus, 4 and metabolic syndrome 5 are more closely associated with ICAS were not confirmed by other studies. 6,7 Hence, the reason for racial or individual differences in the location of cerebral atherosclerosis remains unclear.…”
mentioning
confidence: 99%
“…ICAS is more common in Asians than in Caucasians. 1 Previous studies have addressed the differences in risk factors between ICAS and extracranial atherosclerosis to provide a possible explanation for the racial difference, but the results have been inconsistent; reports that hypertension, 2,3 diabetes mellitus, 4 and metabolic syndrome 5 are more closely associated with ICAS were not confirmed by other studies. 6,7 Hence, the reason for racial or individual differences in the location of cerebral atherosclerosis remains unclear.…”
mentioning
confidence: 99%
“…However, there are accumulating evidences that hemodynamic features as well as stroke mechanisms may differ between ICAS and other stroke subtypes. 24,58,59 Using MRI techniques to understanding pathophysiologies, hemodynamic status, and vascular pathology (via both luminal and wall imaging) will allow the future development of rational stroke therapies for patients with ICAS. As MRI has paved its role in diagnostic angiography.…”
Section: Resultsmentioning
confidence: 99%
“…Among these factors, abnormal glucose regulation was an established risk factors of recurrent stroke in patients with stroke or TIA 24. The physiology underlying the elevated risk of recurrent ischemic stroke in diabetic METS may be that it was a recognized risk factor of intracranial atherosclerosis 25, 26. Previous studies also reported that diabetic METS was associated with recurrent ischemic stroke in patients with large‐vessel infarction or lacunar stroke,10, 17 which we were not able to examine in our study.…”
Section: Discussionmentioning
confidence: 99%